2023
DOI: 10.31557/apjcp.2023.24.2.525
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Pathogenic Germline Mutations in 13 Hereditary Cancer-Related Genes in Breast Cancer Patients in Narathiwat Province, Thailand

Abstract: Background: BRCA1 and BRCA2 genes are known to increase breast cancer's lifetime risk. Early identification of women with this inherited risk can potentially reduce the risk of breast and/or ovarian cancer and, together with early screening, decrease the mortality rate. Objective: This study explored the frequency and distribution of genetic variants in consecutive cases of breast cancer in Narathiwat province, one of the three provinces in the southernmost Thai border. Material & Method: A series of 64 consec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Two unrelated patients with BC diagnosed with TNBC at 28 and 51 years old carried large deletion mutations in BRCA1 c.1863_1885del (p.His621GlnfsTer7). We previously published preliminary information on this in 2023 [26]. Furthermore, we detected novel PVs and LPs in BRIP1, CHEK2, MSH6, PALB2, and PTEN (Table 2) (File S1).…”
Section: Germline Variantmentioning
confidence: 76%
“…Two unrelated patients with BC diagnosed with TNBC at 28 and 51 years old carried large deletion mutations in BRCA1 c.1863_1885del (p.His621GlnfsTer7). We previously published preliminary information on this in 2023 [26]. Furthermore, we detected novel PVs and LPs in BRIP1, CHEK2, MSH6, PALB2, and PTEN (Table 2) (File S1).…”
Section: Germline Variantmentioning
confidence: 76%
“…However, in addition to BRCA1 and BRCA2 , it has been reported that the mutation of the Apolipoprotein B mRNA-editing enzyme, the catalytic polypeptide-like (APOBEC3B) and tumor suppressor gene ( TP53 ) are associated with breast cancer and observed more commonly among Asian women than European women [ 8 , 9 ]. A recent study in Thailand identified the significance of PALB2 and ATM genetic mutations among breast cancer patients as well as BRCA1 and BRCA2 [ 10 ]. The pathogenic mutations of genes ( BRCA1, BRCA2, PALB2, APOBEC3B , and TP53 ) were reported to be associated with the occurrence of breast cancer among Malaysian and Singaporean women [ 11 ] and screening for BRCA1 , BRCA2 , TP53 , and PALB2 genes using blood and saliva samples is currently available in Malaysia [ 12 ].…”
Section: Introductionmentioning
confidence: 99%